12x-3x+90=12x+57

Simple and best practice solution for 12x-3x+90=12x+57 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x-3x+90=12x+57 equation:


Simplifying
12x + -3x + 90 = 12x + 57

Reorder the terms:
90 + 12x + -3x = 12x + 57

Combine like terms: 12x + -3x = 9x
90 + 9x = 12x + 57

Reorder the terms:
90 + 9x = 57 + 12x

Solving
90 + 9x = 57 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
90 + 9x + -12x = 57 + 12x + -12x

Combine like terms: 9x + -12x = -3x
90 + -3x = 57 + 12x + -12x

Combine like terms: 12x + -12x = 0
90 + -3x = 57 + 0
90 + -3x = 57

Add '-90' to each side of the equation.
90 + -90 + -3x = 57 + -90

Combine like terms: 90 + -90 = 0
0 + -3x = 57 + -90
-3x = 57 + -90

Combine like terms: 57 + -90 = -33
-3x = -33

Divide each side by '-3'.
x = 11

Simplifying
x = 11

See similar equations:

| -3(1-v)+4(3v+5)=17 | | -104=-8a-8(1+5a) | | 8a-3(7+10a)= | | 220!/74!(146!) | | x^3-36x+918=0 | | -7(1-5m)+8(4m+5)=33 | | x-[x*37.5/100]=62 | | 15n^2-50n-37=3 | | 1/x=0.04 | | 5(2a-1)+2=-29 | | 3xz+2x+5k=0 | | 63x-(15x-75)=105 | | 5xy-xy-3=0 | | 15x^2+65x+60=0 | | e^4x=9e^3x | | y-x/y | | 2(x-4)+8=20 | | 7(5-2x)=49 | | 2+2x-2=15x+3-13x | | 10(x+4)=4x+2(6-4x) | | 2c+30=60 | | 1/2(2a-4) | | 12=33x+5y | | 6x+3=-[x-10] | | 472=4x^2+16x | | 3x-6-x-4= | | 30+45+13x=150 | | 2cosx+3sinx=1 | | -4x^2+16x-16=0 | | 2cosx+3sin=1 | | 8+3x-2=10x+6-7x | | x^2=4/5 |

Equations solver categories